Prevalence study of human papillomavirus infection in male genital lesions - Cavalcanti, Sílvia M.B. (2001)
Human papillomavirus are the etiological agents of genital cancers. HPV epidemies are increasing worldwide, and are nowadays estimations the most common Sexually Transrmited Disease. Our study ain 10 search for the presence of HPV in biopsies of the male genital troct,by using in situ hybridization. Seventy íive samples were studied and obtained by using peniscopy, afterwards they were classified as condyloma. Papules and acetowhite lesions. The HPV prevalence was 78,7% (59n5). Low risk HPV 6 and 11 were detected in 59,3% (35/59) of the positive lesions and high risk HPVs 16 and 18 were found in 37,3% (22/59). li is important 10 point out lhe detection of high risk HPVs, since male patients are the most important source of infection of The female genital tract, where HPVs fully exerts their potential of maligant transformation.